2018
DOI: 10.1002/jcp.26852
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial pinopode biomarkers: Molecules and microRNAs

Abstract: Ultrastructural changes on the apical surface of the luminal epithelium of the uterus are known as pinopodes. Their morphology in species and in special species is associated with different results about size, duration, and percentage of surface area covered by pinopodes. The content of pinopodes is different in rodents and humans. In mice and rats pinopodes have many vacuoles and no organelle that extends to the actin stalk above the microvilli. Human pinopodes do not have a large vacuole and contain the golg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 128 publications
0
37
0
2
Order By: Relevance
“…The abnormal expression of miRNA has been identified in the majority of human malignancies� including in EC (10), gastric cancer (11), breast cancer (12) and osteosarcoma (13). A variety of studies have demonstrated that miRNA expression is dysregulated in EC, which implicates EC formation and progression by influencing a wide range of biological processes (14)(15)(16). An investigation into the roles of dysregulated miRNAs in EC may therefore be useful in the future development of therapeutic targets for patients with this disease.…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal expression of miRNA has been identified in the majority of human malignancies� including in EC (10), gastric cancer (11), breast cancer (12) and osteosarcoma (13). A variety of studies have demonstrated that miRNA expression is dysregulated in EC, which implicates EC formation and progression by influencing a wide range of biological processes (14)(15)(16). An investigation into the roles of dysregulated miRNAs in EC may therefore be useful in the future development of therapeutic targets for patients with this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Beside demonstrating by TEM analysis that this in vitro culture recapitulates well the in vivo glandular architecture according to the different cycle's phases, SEM analysis gave us the opportunity to provide clear evidence for the presence of pinopodes at the luminal surface of the in the secretory phase-induced organoids. Many reports suggested pinopodes as reliable key features of the implantation window, the limited time frame when endometrium is fully receptive to blastocyst implantation [32]. To the best of our knowledge, this is the first time that this peculiar cellular morphology, strictly related to the topographic localization on the implantation site, is recapitulated in an in vitro model of human endometrium.…”
Section: Discussionmentioning
confidence: 70%
“…The luminal surface of endometrial ORG-msp but not ORG-pp is characterized by the presence of large apical cytoplasmic protrusions traditionally called "pinopodes". Their presence is reported to be a specific marker of the implantation window [32] and is therefore an important and novel feature of hereby described ex vivo endometrial model. Pinopodes bulge out of the entire adluminal cell surface, have regular contours and are characterized by a significant loss of free surface micro-extensions, including cilia and microvilli ( Figure 3D,E).…”
Section: Established Human Endometrial Epithelial Organoids Respond Tmentioning
confidence: 85%
“…В группе белков клеточной адгезии есть и другие молекулы, кроме интегрина αvβ3, которые рассматривают в качестве способных влиять на рецептивность эндометрия: CD44, trophinin, cadherin-11 [83][84][85]. Другие возможные маркеры, определяющие рецептивное состояние эндометрия, включают: цитокин LIF (leukemia inhibitory factor -ингибирующий фактор лейкемии), факторы роста HB-EGF (heparin-binding epidermal growth factor-like factor -гепаринсвязывающий EGF-подобный фактор роста) и IGF-II (insulin-like growth factor-II -инсулиноподобный фактор роста-II) [20,23,32,86], кальцитонин [74,75], транскрипционные факторы HOXA10 и HOXA11 [76,[87][88][89], L-селектин и лиганд L-селектина [90].…”
Section: иммуногистохимические исследованияunclassified